Impairment in Respiratory Function Contributes to Olfactory Impairment in Amyotrophic Lateral Sclerosis - Günther, René; Schrempf, Wiebke; Hähner, Antje; Hummel, Thomas; Wolz, Martin; Storch, Alexander; Hermann, Andreas (Frontiers in Neurology, 2018)
Background: Non-motor symptoms are very common in neurodegenerative diseases. In patients suffering from Amyotrophic Lateral Sclerosis (ALS) olfactory dysfunction was first reported more than 20 years ago, however, its pathophysiological correlate and further implications remains elusive. Methods: In this so far largest case control study we analyzed olfactory performance with the ‘Sniffin’ Sticks’, a validated olfactory testing kit used in clinical routine. This test kit was designed to investigate different qualities of olfaction including odor threshold, odor discrimination and odor identification. Results: ALS patients were mildly but significantly impaired in ‘TDI score’, the composite of the 3 subtests (ALS 27.7±7.9, Controls 32.3±5.8). In contrast to Parkinson’s disease, ALS patients did not show impaired performance in the suprathreshold tests identification and discrimination. However, the odor threshold was markedly decreased (ALS 6.0±3.4, Controls 8.77±3.6). This pattern of olfactory loss resembles sinonasal diseases, where olfactory dysfunction results from impeded odorant transmission to the olfactory cleft. Evaluation of medical history and clinical data of ALS patients showed that patients with perception of dyspnea (TDI 25.7±8.0) performed significantly worse in olfactory testing compared to those who did not (TDI 30.0±7.4). In line with that, we found that in patients with preserved respiratory function (vital capacity >70% of index value) olfactory performance did not differ from healthy controls. Conclusions: These findings suggests, that the mild impairment of olfaction in patients suffering from ALS should at least partly be considered as a consequence of impaired respiratory function and might be a marker of respiratory dysfunction in ALS.